Cervical cytology and the diagnosis of cervical cancer in older women. (December 2015) - Landy, Rebecca; Castanon, Alejandra; Dudding, Nick; Lim, Anita Wey Wey; Hollingworth, Antony; Hamilton, Willie; Sasieni, Peter D
Objectives: Most non-screen-detected cervical cancers are advanced stage. We assess the potential for cytology to expedite diagnosis when used outside of routine call and recall screening for cervical cancer. Methods: Two cohorts of women with cytology that did not appear to have been taken as part of routine screening, nested within a census of cervical cytology, in England between April 2007 and March 2010 were studied: 93, 322 women aged 40–69 at first cytology, and 14, 668 women aged ≥70. The diagnostic performance of high grade cervical squamous intraepithelial lesion (HSIL) or worse cytology was estimated. We also estimated case-fatality from stage distribution in women aged ≥66 with and without cytology in the year prior to diagnosis. Results: There were 259 cancers diagnosed in women aged 40–69 at first cytology, and 78 in women aged ≥70. The sensitivity of cytology ≥ HSIL for cancer was 89% and 83% respectively, and the number of women needed to test to identify one cancer was 404 (95% confidence interval [CI]: 355–462) and 226 (95% CI: 177–292) respectively. Women aged ≥66 with cytology within a year of diagnosis had earlier stage cancers than those without, corresponding to a 17–22% reduction in case fatality. Conclusions: Cervical cytology is an excellent identifier of cancer among women tested outside routine screening call and recall. Its use as a triage tool, for instance in women with vague gynaecological symptoms, could facilitate earlier stage diagnosis and reduce cervical cancer mortality.